Orientation-dependent indentation response of magnesium single crystals: Modeling and experiments - Selvarajou, Balaji; Shin, Joong-Ho; Ha, Tae Kwon; Choi, In-suk; Joshi, Shailendra P.; Han, Heung Nam (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
We investigate the orientation-dependent characteristics of magnesium single crystals under localized contact using nanoindentation experiments and crystal plasticity finite element (CPFE) simulations. Nanoindentation experiments on (0 0 0 1) and (1 1 (2) over bar 0) planes exhibited distinct load depth responses. Atomic force microscopy revealed material pile-up with sixfold symmetry in the former case and a sink-in phenomenon with twofold symmetry in the latter case. Our corresponding detailed CPFE simulations uncover the evolution of deformation activity in the indented volume, thereby providing insight into the interacting effects that cause the pile-up and sink-in phenomena. The simulations indicate the occurrence of {1 0 (1) over bar 2} extension twins in both cases, although their spatial locations are different. These observations strongly corroborate with our transmission electron microscopic analysis of the indented samples. Finally, our simulations also indicate that, depending upon the crystal orientation, elastic recovery upon unloading may play important role in final surface morphology around the indented region. (C) 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: PLASTICALLY GRADED MATERIALS; FINITE-ELEMENT SIMULATIONS; PYRAMIDAL INDENTATION; SPHERICAL INDENTATION; SURFACE DEFORMATION; HEXAGONAL METALS; ELASTIC-MODULUS; GRAIN-SIZE; PILE-UP; NANOINDENTATION